2022
DOI: 10.3389/frsc.2022.751681
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Urban Governance Parameters for Online Learning in Saudi Arabia During COVID-19 Using Topic Modeling of Twitter Data

Abstract: Smart cities are a relatively recent phenomenon that has rapidly grown in the last decade due to several political, economic, environmental, and technological factors. Data-driven artificial intelligence is becoming so fundamentally ingrained in these developments that smart cities have been called artificially intelligent cities and autonomous cities. The COVID-19 pandemic has increased the physical isolation of people and consequently escalated the pace of human migration to digital and virtual spaces. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The architecture's modules will be presented in Sections Data Collection and Storage, Data Preprocessing, Parameters Discovery (Education Governance), Validation, and Visualization and Reporting. Additional details about the general methodology related to this study can be found in the study of Alswedani et al (2022).…”
Section: Methodology and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture's modules will be presented in Sections Data Collection and Storage, Data Preprocessing, Parameters Discovery (Education Governance), Validation, and Visualization and Reporting. Additional details about the general methodology related to this study can be found in the study of Alswedani et al (2022).…”
Section: Methodology and Designmentioning
confidence: 99%
“…This work is an extension of our earlier work that had considered 128 thousand tweets for a 66-days period from October 2020 to December 2020 (Alswedani et al, 2022). The work presented in this study makes substantial improvements to the data collection process and overall methodology, including the collection of around 2 million tweets for a period of 14 months (October 2020-December 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Zhou et al [31] provided a cross-sectional study that investigates the prevalence rates of depression and anxiety, as well as their socio-demographic correlation, among Chinese high school students between 12-18 years who got affected by the COVID-19 pandemic. Alswedani et al also reported evidence for psychological stress among students, educators, and parents during COVID-19 [32], [33]. Other studies that reported psychological effects of COVID-19 include [34], [35].…”
Section: Covid-19 and Psychological Healthmentioning
confidence: 97%
“…Saurs et al [53] used data mining techniques to identify the main security concerns in smart living environments. Many research have done on discovering COVID-19 issues using Twitter data analytics [54], [55]. For instance, Su et al [56] used to investigate the spatial-temporal factors and socioeconomic disparities that shaped U.S. residents' responses to COVID-19.…”
Section: Related Workmentioning
confidence: 99%